Comparison of inter- and intraobserver agreement between [18F]AlF-NOTA-octreotide and [68Ga]Ga-DOTA-SSA PET/CT - Hannes Leupe; Niloefar Ahmadi Bidakhvidi; Karolien Goffin; Bliede Van den Broeck; Sander Jentjens; Annouschka Laenen; Elin Pauwels; Willem Lybaert; Eric Van Cutsem; Guy Bormans; Timon Vandamme; Frederik Cleeren; et al. (EJNMMI Reports)
Abstract Purpose This study compares inter- and intraobserver agreement between [18F]AlF-NOTA-octreotide ([18F]AlF-OC) and [68Ga]Ga-DOTA-somatostatin analogues (SSAs) in PET/CT imaging for neuroendocrine neoplasm (NEN) patients. Materials and methods This is a secondary endpoint analysis from our multicenter trial (clin trial.gov identifier: NCT04552847) including 75 NEN patients who received both [68Ga]Ga-DOTATATE (n = 56) or [68Ga]Ga-DOTA-NOC (n = 19) and [18F]AlF-OC PET imaging. Five readers assessed lesion detection and characterization across multiple organs, scoring lesions by number and conspicuity using a 5-point Likert scale. Agreement was measured using Gwet’s agreement coefficient. Results Results demonstrated nearly perfect interobserver agreement for lesion characterization across all organs for both tracers (0.921 for [18F]AlF-OC; 0.934 for [68Ga]Ga-DOTA-SSA). Similar agreement was observed for the number of lesions across organs (0.736 for [18F]AlF-OC and 0.749 for [68Ga]Ga-DOTA-SSAs). Organ-specific analysis revealed strong agreement for bone and liver lesions, with slightly lower agreement for lymph nodes. Both tracers also showed excellent agreement in determining Krenning scores (0.925 for [18F]AlF-OC and 0.927 for [68Ga]Ga-DOTA-SSAs). While mean lesion conspicuity was similar between tracers, [18F]AlF-OC had a higher global image quality score (4.22 vs. 3.86, p < 0.0001). Intraobserver agreement was consistent between tracers for lesion characterization (> 0.95 for both readers) and lesion count (> 0.80 for both readers). Conclusion [18F]AlF-OC and [68Ga]Ga-DOTA-SSAs demonstrate comparable and excellent inter- and intraobserver agreement, reinforcing the clinical interchangeability of [18F]AlF-OC PET/CT with [68Ga]Ga-DOTA-SSAs in routine practice.